PENGEMBANGAN KEMAMPUAN LITERASI NUMERASI MATEMATIKA SISWA KELAS VI SDN TAENG DENGAN MENGGUNAKAN METODE DRILL: Penelitian Tindakan Kelas - Ilmi Ramdana Ishak; Fitri Wahid; Hilmi Hambali (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Development of Mathematical Numeracy Literacy Skills of Grade VI Students of SDN TAENG Using the Drill Method. Makassar: Faculty of Teacher Training and Education, Muhammadiyah University of Makassar, 2024.The purpose of this study was to determine the development of mathematical numeracy literacy skills of grade VI students of SDN TAENG using the drill method. This study is a classroom action research using a modification of the Kemmis and Taggart model with 2 cycles. The subjects of this study were 37 students. Data collection techniques used observation, tests, and questionnaires. The results showed that students' numeracy literacy skills in cycle I were 3.85% with high category scores, 61.54% with medium category scores, and 34.61% with low category scores. In cycle II, there was a development with a percentage of 88.46% of students getting high category scores, 3.85% with medium category scores, and 7.69% with low category scores. For the student response questionnaire from cycle I to cycle II there was a development with a percentage of 78.27% to 92.04% with a very high category, as well as the percentage of student activity increased from cycle I to cycle II with a percentage of 87.98% increasing to 96.64% with a very good category, for the percentage of teacher activity of 93.27% in cycle I, 97.12% cycle II with a very good category. This can be stated that the success indicator has been achieved in cycle II. Thus, students' numeracy literacy skills can be improved by using the drill method.